2004
DOI: 10.2139/ssrn.1818719
|View full text |Cite
|
Sign up to set email alerts
|

Search Methods and Outcomes in Developing Countries: The Case of Venezuela

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…For example, more than 72% of those who work in the shadow economy and more than 52% of those who work in the formal sector rely on the social networks to move from one sector to another in Venezuela (Marquez and Ruiz-Tagle, 2004). These networks payoff only when someone is already unemployed for a while (Marquez and Ruiz-Tagle, 2004;Gong et al, 2004;Serneels, 2007).…”
Section: Sectoral Labor Mobilitymentioning
confidence: 99%
“…For example, more than 72% of those who work in the shadow economy and more than 52% of those who work in the formal sector rely on the social networks to move from one sector to another in Venezuela (Marquez and Ruiz-Tagle, 2004). These networks payoff only when someone is already unemployed for a while (Marquez and Ruiz-Tagle, 2004;Gong et al, 2004;Serneels, 2007).…”
Section: Sectoral Labor Mobilitymentioning
confidence: 99%
“…Márquez and Ruiz-Tagle (2004) study employment mobility in Venezuela as an input for contrasting job search models in Latin America.…”
Section: E C O N O M I a Spring 2007mentioning
confidence: 99%
“…On the contrary, Beine's (2009) analysis of a bilateral data set on international migration by educational attainment from 195 countries to 30 OECD countries in 1990-2000 shows that less educated and longer-term unemployed workers and workers who were fired from previous jobs tend to rely more on employment agencies and social contacts (Gregg and Wadsworth, 1996;Heath, 1999;Korpi, 2001;Larsen, 2008;Marquez and Ruiz-Tagle, 2004;Weber and Mahringer, 2007). However, Addison and Portugal (2002) concluded that low skilled and less educated emigrants in Portugal used employment agencies unequally.…”
Section: H7: Formal Job Search Methods Results In Higher Chances Of Fimentioning
confidence: 99%
“…Using the case of Venezuela, Marquez and Ruiz-Tagle (2004) suggest that more educated workers tend to use mostly formal job search methods, especially in form of advertisements. In addition, they argue that workers who are employed in formal, full-benefits jobs are most likely to use formal job search methods which also result in higher chances of finding a formal job (Marquez and Ruiz-Tagle, 2004). Basker (2003) in his study on the job search and education explains that higher-skilled emigrants expect higher returns from their job search.…”
Section: Social Network and Job Search Strategies Of Migrantsmentioning
confidence: 99%
See 1 more Smart Citation